2013
DOI: 10.1039/c3ra41034j
|View full text |Cite
|
Sign up to set email alerts
|

Centimeter-scale giant spherulites in mixtures of polar polymers and crystallizable diluents: Morphology, structure, formation and application

Abstract: A series of giant spherulites at centimetre scale were effectively constructed from the mixtures of polyacrylonitrile (PAN)/dimethyl sulfone (DMSO2), although neither PAN nor DMSO2 itself forms spherical morphology during crystallization. A detailed investigation was carried out on the morphology, microstructure, and formation mechanism by polarized optical microscopy, scanning electron microscopy, wide-angle X-ray diffraction, polarized FTIR spectroscopy, and differential scanning calorimetry. These giant sph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 49 publications
0
4
0
Order By: Relevance
“…Interestingly, the hydz-Si 16 -hydz, hydz-Si 24 -hydz, and hydz-Si 15 block molecules grow spherulites with sizes up to 5 mm from one nucleation point (Figure 1F). This has been reported occasionally for mixtures of polymers and small molecules, 47,48 but for oligomers with covalently attached small molecule end-groups, such large textures have not been reported to date. The nucleation point for spherulite growth appeared on millisecond time scales, which gives a first hint that a very fast thermal phase transition occurs in these systems.…”
Section: Resultsmentioning
confidence: 89%
“…Interestingly, the hydz-Si 16 -hydz, hydz-Si 24 -hydz, and hydz-Si 15 block molecules grow spherulites with sizes up to 5 mm from one nucleation point (Figure 1F). This has been reported occasionally for mixtures of polymers and small molecules, 47,48 but for oligomers with covalently attached small molecule end-groups, such large textures have not been reported to date. The nucleation point for spherulite growth appeared on millisecond time scales, which gives a first hint that a very fast thermal phase transition occurs in these systems.…”
Section: Resultsmentioning
confidence: 89%
“…These periodic ring textures can be controlled from 600 nm to >15 mm, 29,77,78 and some polymeric spherulites can grow up to 4 cm in dimensions. 79 Thus, these RBSs can serve as template substrates for replicate-manufacturing wrinkled textures with custom-made patterns. Tuning the height profile with an optimal inter-band space can produce desired photonic reflection from the RBS crystallized and cast as thin films.…”
Section: Introductionmentioning
confidence: 99%
“…Height profiles of the RBS top surface may differ with respect to annealing, crystallization temperature, etc. These periodic ring textures can be controlled from 600 nm to >15 mm, ,, and some polymeric spherulites can grow up to 4 cm in dimensions . Thus, these RBSs can serve as template substrates for replicate-manufacturing wrinkled textures with custom-made patterns.…”
Section: Introductionmentioning
confidence: 99%
“…2,4 ECTFE is insoluble in all known solvents at room temperature; 5 the fabrication of ECTFE membranes is not feasible via conventional methods such as the solution phase inversion method. However, since ECTFE is soluble in selected solvents at elevated temperatures, it is possible to fabricate membranes via the thermally induced phase separation (TIPS) process, which is a useful technique for the preparation of polymeric membranes and has been applied to many polymers, such as PP, [6][7][8] PE, 9,10 PAN 11,12 and PVDF. [13][14][15][16] A few studies have been reported on the preparation of ECTFE microporous membranes via TIPS.…”
Section: Introductionmentioning
confidence: 99%